CONTEMPORARY SUPERCONDUTIVITY MATERIALS - D. Lj. Mirjanić; J. P. Šetrajčić (Journal of Engineering & Processing Management, 2009)
In this paper will be introduced the newest research in high-temperature superconducting materials. In the first part of the paper will be analyzed discovery of superconductivity and the phenomena and effects related with this topic and the superconducting materials as well. In the second part of the paper will be analyzed our research of nanostructure superconductivity, where we will introduce the model of the ultra-thin films, quantum wires and quantum dots. In the end, we will analyze thermodynamic and transport properties, achieved results and perspectives for the future research.
Keywords: nanostructuralmaterials; superconductors